Hyperthermia combined with immune checkpoint inhibitor therapy in the treatment of primary and metastatic tumors - Yang, Ximing; Gao, Miaozhi; Xu, Runshi; Tao, Yangyang; Luo, Wang; Wang, Binya; Zhong, Wenliang; He, Lan; He, Yingchun (Frontiers in Immunology, 2022)
According to the difference in temperature, thermotherapy can be divided into thermal ablation thermotherapy and mild hyperthermia. The main advantage of thermal ablation hyperthermia is that it can efficiently target tumors in situ, while mild hyperthermia has a good inhibitory effect on distant metastasis. There are some similarities and differences between the two therapies with respect to inducing anti-tumor immune responses, but neither of them results in sustained systemic immunity. Malignant tumors (such as breast cancer, pancreatic cancer, and nasopharyngeal carcinoma, and brain cancer) are recurrent, highly metastatic, and highly invasive even after treatment, hence a single therapy rarely resolves the clinical issues. A more effective and comprehensive treatment strategy using a combination of hyperthermia and immune checkpoint inhibitor (ICI) therapies has gained attention. This paper summarizes the relevant preclinical and clinical studies on hyperthermia combined with ICI therapies and compares the efficacy of two types of hyperthermia combined with ICIs, in order to provide a better treatment for the recurrence and metastasis of clinically malignant tumors.